Dampak Akuisisi Terhadap Profitabilitas Perusahaan Menurut Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas - Tsabitha, Andara; Rahmadhani, Aulia; Pebrianti, Kalista Revana; Zakaria, Salsabila Anggraini (Media Hukum Indonesia (MHI), 2024)
In an era of increasingly tight free competition, companies are encouraged to find ways to develop strategies in order to survive. Acquisition has become a popular business expansion strategy used by companies to maintain their existence and survival. This article was written with the aim of finding out more about the legal provisions on the company acquisition process in Indonesia and its impact on company profitability. The method used in this writing is to use the normative legal method, which prioritizes library materials. Finally, it can be concluded that the company acquisition process in Indonesia which is based on Law Number 40 of 2007 concerning Limited Liability Companies can go through two stages, namely through the company's board of directors and direct acquisition from shareholders. Acquisitions can have a significant impact on company profitability by increasing operational efficiency, creating synergies, and expanding market share. Through acquisitions, companies can optimize financial ratios such as ROE, ROI, GPM, OPM, and NPM, which reflect the company's ability to generate profits and maximize value for shareholders.